The Phonetic Challenges of Vowel Elision for Nigerian Students of French for Specific Purpose (FOS) (International Journal of Scientific Research and Management (IJSRM), 2024)
This article examines the specific phonetic challenges faced by Nigerian students in French vowel elision for specific purpose (FOS). The study analyzes the difficulties related to vowel elision, a phonetic process crucial for the acquisition of advanced linguistic skills in FOS. The research methodology includes classroom observations, student assessments, and interviews with students and teachers, providing in-depth analysis of error patterns and contributing factors. The results show that the main obstacles come from the interference of mother tongues (L1), insufficient phonetic training and a lack of awareness of the nuances of French phonology. The study proposes suitable teaching strategies, focusing on targeted phonics training and awareness activities, to improve the effectiveness of FOS teaching for Nigerian students. Implications for teaching practice and future research are discussed.